How Self-Efficacy Influences Traffic Police Performance: The Mediating Role of Organizational Commitment in Indonesia ? - Muh. Asdar; Mamat Rahmat; Dedy Darmawan (Vifada Management and Social Sciences, 2026)
Purpose: This study examines the mediating role of organizational commitment in the relationship between self-efficacy and the performance of traffic police officers in Indonesia. It hypothesizes that self-efficacy positively influences performance both directly and indirectly through organizational commitment. Research Design and Methodology: A quantitative approach with a causal research design was employed. Data were collected through a structured questionnaire from 300 traffic police officers working in several major cities across Indonesia. The constructs of self-efficacy, organizational commitment, and performance were measured using validated and reliable instruments. Structural Equation Modeling (SEM) was utilized to test the proposed relationships and mediation effect. Findings and Discussion: The results reveal that self-efficacy has a significant positive effect on traffic police performance (β = 0.30, p < 0.001) and organizational commitment (β = 0.45, p < 0.001). Organizational commitment also significantly enhances performance (β = 0.40, p < 0.001). Furthermore, organizational commitment partially mediates the relationship between self-efficacy and performance, indicating that officers with higher confidence in their capabilities tend to develop stronger commitment, which subsequently improves their work performance. Implications: The findings suggest that police organizations should strengthen officers’ self-efficacy through continuous training and professional development while fostering organizational commitment through supportive human resource policies and employee engagement initiatives. These efforts may contribute to improved service effectiveness, organizational performance, and public safety outcomes.